2012
DOI: 10.1186/1471-2202-13-134
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and behavioural changes occur following the X-ray irradiation of the adult mouse olfactory neuroepithelium

Abstract: BackgroundThe olfactory neuroepithelium lines the upper nasal cavity and is in direct contact with the external environment and the olfactory bulbs. The ability to self-renew throughout life and the reproducible recovery after injury, make it a model tissue to study mechanisms underlying neurogenesis. In this study, X-rays were used to disrupt proliferating olfactory stem cell populations and to assess their role in the cellular and morphological changes involved in olfactory neurogenic processes.ResultsWe hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Despite the olfactory controls in place, odor cues might have been used in part to perform the discrimination task in this study. If so, this would be more properly assessed by olfactory threshold testing as there is evidence that olfactory epithelium is susceptible to irradiation damage at the 8 Gy dose used in this experiment (Ophir et al 1988;Cunha et al 2012). The spike in threshold increases on day 11 also suggests there may be other mechanisms involving cell renewal which need further exploration.…”
Section: Discussionmentioning
confidence: 95%
“…Despite the olfactory controls in place, odor cues might have been used in part to perform the discrimination task in this study. If so, this would be more properly assessed by olfactory threshold testing as there is evidence that olfactory epithelium is susceptible to irradiation damage at the 8 Gy dose used in this experiment (Ophir et al 1988;Cunha et al 2012). The spike in threshold increases on day 11 also suggests there may be other mechanisms involving cell renewal which need further exploration.…”
Section: Discussionmentioning
confidence: 95%
“…There was no difference in apoptosis in the olfactory epithelium between the irradiation and control groups. Reduced neurogenesis, small olfactory bulbs, changes in the subtypes of the interneurons connecting the olfactory epithelium to the olfactory bulbs, and a significant reduction in GABAergic subtypes have been observed [72,73].…”
Section: Radiation-induced Taste and Smell Impairmentmentioning
confidence: 99%
“…), then shielded with lead so that only their heads and necks would receive irradiation. Eight Gy of X-ray was administered by an RS 2000 Biological Irradiator (Rad Source Technologies, Inc.) in accordance with published studies that showed this amount of radiation induces changes in olfactory neuroepithelium without being lethal to the animals under study (Cunha et al 2012;Nguyen et al 2012). Because Cunha et al showed disruption in Bowman's glands and the basal lamina 1-week post 8 Gy irradiation, we chose this as our survival time point.…”
Section: Irradiationmentioning
confidence: 99%
“…We did not observe any effects of radiation exposure on mucin expression at the 1-week time point. We selected a single 8 Gy dose because this has been shown to alter cellular function within mouse olfactory and taste mucosa without resulting in excess mortality (Cunha et al 2012;Nguyen et al 2012). At 1-week post irradiation, Cunha et al reported changes in mouse nasal mucosal morphology as well as olfactory performance as measured by behavioral testing.…”
Section: Effects Of Radiationmentioning
confidence: 99%